PERILAKU EKONOMI ETNIS CINA DI INDONESIA SEJAK TAHUN 1930-AN - Ali Padang Siregar (Jurnal Education and Development, 2018)
This economic behavior ultimately leads to a business that is safe and neutral in the sense that it does not pose much risk to the safety and well-being of the self. The concrete form of ethnic Chinese economics tends to move in the field of retail and financial, business that is not a big business (because the vital efforts of its management are controlled by the state). Economic behavior that tends to be proactive, in the form of business or family company, has become characteristic of ethnic Chinese in Asian region including Indonesia. This is also supported by ethnic Chinese perception to the identification of ethnic Chinese against state inhabited. Particularly in Indonesia, the ethnic Chinese economic perception is divided between the economic and ethnic Chinese perceptions of "totok" and the early peranakans are both present as overseas Chinese. This condition is exacerbated by the attitude of some bureaucrats or high-ranking Indonesian officials who tend to prefer cooperation with ethnic Chinese to run their business, because Chinese ethnicians are considered more experienced and strong capital than natives. Indeed, it has been proved that the majority of emigrants are more successful than ethnic Chinese peranakans, the cause of "totok" ethnic Chinese tend to be innovative and dare to take high risks as entrepreneurs, while ethnic Chinese peranakans are more conservative in business, which tend to be more interested in becoming professionals rather than entrepreneurs.